2021
DOI: 10.1111/inr.12716
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, physical, and social effects of the COVID‐19 pandemic on hospital nurses

Abstract: Aim The study aim was to explore the physical, mental, and social effects of the COVID‐19 pandemic on Austrian nurses working in hospitals. Background The COVID‐19 pandemic required nurses to work extremely hard and over long periods, which can have physical, psychological, and social consequences. Methods This study was carried out using a qualitative descriptive design and data was collected through individual interviews using an interview guide. A qualitative content analysis was conducted taking both deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…32 In a study, all of the nurses stated they experienced social isolation and their use of social media increased. 33 In our study, most of the nurses stated the use of social distance and protective equipment weakened the communication between the team. The nurses thought that team communication throughout the surgical process was very motivational, and poor communication caused anxiety.…”
Section: Effect Of Transmission Risk On Surgical Team Communicationmentioning
confidence: 62%
“…32 In a study, all of the nurses stated they experienced social isolation and their use of social media increased. 33 In our study, most of the nurses stated the use of social distance and protective equipment weakened the communication between the team. The nurses thought that team communication throughout the surgical process was very motivational, and poor communication caused anxiety.…”
Section: Effect Of Transmission Risk On Surgical Team Communicationmentioning
confidence: 62%
“…Evidence has recognized social media as cathartic instruments for mitigating stress and loneliness in nurses living during the COVID-19 pandemic. 42 As emerged during the first wave, 17 and in the second/ third wave, nurses reported some details (e.g. age, gender and unit) in almost half of their posts, confirming the desire to share their experiences openly and transparently.…”
Section: Narrativesmentioning
confidence: 81%
“…Evidence has recognized social media as cathartic instruments for mitigating stress and loneliness in nurses living during the COVID-19 pandemic. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Of the nurses, 84.4% had redness or scars on their face due to the use of N95 masks, and 52.8% of them had wounds on their foreheads due to the front wall of the visors (Table 2). In the study of Häussl et al, 13 one of the most commonly reported physical problems in nurses was skin rash. Lan et al 10 detected skin problems in the cheek area of 78.7% and forehead area of 57.2% of healthcare workers managing the COVID‐19 disease 10 .…”
Section: Discussionmentioning
confidence: 99%